Penerapan Metode Cerita Bernuansa Islami Dalam Penanaman Akhlak Mulia Peserta Didik Pada Mata Pelajaran PAI - Sri Indah Triani; Syafa'atun Nahriyah; Abu Syhabudin (Indonesian Journal of Islamic Education, 2023)
The low noble character of students is one of the fokus problem in this study. This study aims (1) to find out the results of cultivating noble morals in students before using the story method with Islamic nuances, (2) to find out the results of instilling noble morals in students after using the story method with Islamic nuances, (3) to find out the responses of students after using the method a story with Islamic nuances in cultivating noble character in class V at SDN Panongan 1, Jatipuh District, Majalengka Regency. This type of research is a qualitative method with a class action research design (CAR). As a research subject, namely class V SDN Panongan 1 with a total of 15 people. The research instruments used were observation, interviews, documentation, pre-test and post-test. The data analysis technique used is data reduction technique, data presentation, and verification (conclusion drawing). The results of this study are as follows (1) the implementation of learning using the story method with Islamic nuances is in accordance with the procedure for implementing learning, (2) increasing the values the class average on the initial test was 54.4% with a learning percentage rate of 13.3%. In cycle I, the class average score was 76 with a learning completeness level of 46.67%. And the second cycle has an average value of 85.33 with a complete learning of 80%. (3) improve learning outcomes in inculcating students' noble character with initial tests up to cycle II.